Optimal Design of Diversion Piers of Lateral Intake Pumping Station Based on Orthogonal Test - Jiren Zhou; Miaomiao Zhao; Chuan Wang; Zhenjun Gao (Shock and Vibration)
To explore the rectification parameters of the diversion piers optimized for the forebay of the pump station with a lateral angle of 45°, the orthogonal experiment and computational fluid dynamics methods are used to analyze the flow characteristics of the diversion piers under different parameter combinations. The flow pattern in the forebay of the side water inlet is improved. The rectification effect of the diversion piers under 16 schemes is analyzed, considering the length, width, radian, and relative height of the diversion piers. Combined with numerical simulation, a better rectification scheme is provided, and finally, a reasonable range of values for the rectification parameters of the forebay diversion pier of the side 45° bend angle pump station is obtained.